Development of scientific inquiry, from an authentic task with the petroglyph of the Wak’a of Suyo - Taipe, Franklin (2021)
The purpose was to develop the competence investigates through scientific methods with content analysis, to build new knowledge in the area of science in three groups of teachers with the task of authenticating “possible explanations of the message of the Wa’ka de Suyo petroglyph”. Using basic research teaching-learning methodology. Developing in three stages: initiation with the field visit for motivation, measurements and interviews; development with the scientific inquiry of content analysis; completion to expose and discuss the validation of your guesses. The result of the astronomical aspect explains the analogy of the circles with binary star systems, the meteorological aspect explains the similarity with the cloud-earth and earth-cloud rays and with the ascending rays, of the biological aspect of conjecture reproductive cells does not reach similar findings. The development of the competence was achieved from the inquiry by content analysis motivated by the authentic task.